2003
DOI: 10.1001/archinte.163.19.2354
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Serotonergic Antidepressants and Need for Blood Transfusion in Orthopedic Surgical Patients

Abstract: Use of serotonergic antidepressants is associated with an increased risk of bleeding and subsequent need for blood transfusion during orthopedic surgery. The bleeding could be attributed to inhibition of serotonin-mediated platelet activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
112
1
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(129 citation statements)
references
References 36 publications
9
112
1
4
Order By: Relevance
“…Since then, several other studies have reported an association between SSRI use and spontaneous upper gastrointestinal hemorrhage [8] . A case-control study by Meijer et al, [4] observed a 2.6 fold increased risk of gastrointestinal bleeding events in patients receiving SSRI medications and the findings of this study were similar to the initial 1999 report of de Abajo et al [7] Platelet aggregation is essential for hemostatic thrombus formation, and this process requires the release of serotonin from the platelets [1,9] . Serotonin, is a neurotransmitter hormone (5-hydroxytryptamine, 5-HT), which is primarily stored in the blood platelets (99%), in the enterochromaffin cells of the intestines, and the neurons in the central nervous system [1,9,10] .…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…Since then, several other studies have reported an association between SSRI use and spontaneous upper gastrointestinal hemorrhage [8] . A case-control study by Meijer et al, [4] observed a 2.6 fold increased risk of gastrointestinal bleeding events in patients receiving SSRI medications and the findings of this study were similar to the initial 1999 report of de Abajo et al [7] Platelet aggregation is essential for hemostatic thrombus formation, and this process requires the release of serotonin from the platelets [1,9] . Serotonin, is a neurotransmitter hormone (5-hydroxytryptamine, 5-HT), which is primarily stored in the blood platelets (99%), in the enterochromaffin cells of the intestines, and the neurons in the central nervous system [1,9,10] .…”
Section: Introductionsupporting
confidence: 85%
“…There was no significant difference in the three outcome measures of change in hematocrit, estimated blood loss, and perioperative transfusion requirements between patients who used serotonergic antidepressants and those who did not. In the study of Moving et al [4] . The study population consisted of patients who underwent a variety of orthopedic surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of the encouraging safety profile of SSRIs, there have been several studies suggesting that SSRIs may cause bleeding abnormalities in orthopedic procedures, mostly following hip and knee arthroplasty [3,4]. A possible mechanism for this effect involves the inhibition of serotonin reuptake into platelets, as serotonin weakly potentiates platelet aggregation and hemostasis [5].…”
Section: Introductionmentioning
confidence: 99%